Overseas Education in China: Changing Landscape and Policies - Jiang, Kai; Ma, Xueni (International Higher Education, 2011)
While China becomes a major country that sends students abroad, overseas education in China has experienced a rapid development. Overseas education brings political, cultural, educational and economic gains. There are also challenges that will require changes in policies.